ASSOCIATION BETWEEN ANEMIA AND FIRST-TIME FEBRILE SEIZURE: A CASE CONTROL STUDY - Handoyo (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Introduction: Febrile seizure is the most frequent neurological disorder in children below five years old. The direct cause is unknown. Some studies report association between anemia and febrile seizure. Even though anemia is highly prevalent in Indonesia, only one study assessed this association. Objective: To compare the hemoglobin level in children with febrile seizure and febrile children without seizure, and to assess the relationship between anemia and febrile seizure. Method: This retrospective case control study used medical record of febrile children aged 6 months to 3 years old hospitalized at Landak General Hospital between May 2016 to April Hemoglobin level from first laboratory examination then compared between fifty children with first-time febrile seizure (case group) and a hundred febrile children without seizure (control group). Results: Hemoglobin level was lower in case group compared to control group (p<0,001). Children with febrile seizure were more likely to be anemic compared to febrile children without seizure [OR 6,73; 95% CI 3,18 to 14,26]. Conclusion: There is a significantmean difference between hemoglobin level of children with febrile seizure compared to febrile children without seizure. Children with febrile seizure were six times more likely to have anemia.